Quality of life in patients with leg ulcers or skin lesions – a pilot study - Szewczyk, Maria T.; Mościcka, Paulina; Jawień, Arkadiusz; Cwajda-Białasik, Justyna; Cierzniakowska, Katarzyna; Ślusarz, Robert; Hancke, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Attempts to determine the quality of life are advisable in patients with ulcers as the group affected with this problem is relatively large. According to one Polish randomized trial, approximately 0.3–2% of the adult population suffers from active or healed venous ulcers. Aim: To compare the quality of life of patients with leg ulcers of venous and arterial etiology and those with lower limb skin lesions due to chronic venous insufficiency. Material and methods: This study included 90 consecutive patients with ulcers of venous (n = 30) or arterial etiology (n = 30), or patients with trophic disorders of the skin associated with chronic venous insufficiency (n = 30) treated at the Venous Ulceration Outpatient Clinic and at the Department and Clinic of General Surgery, Dr. J. Biziel Memorial University Hospital No. 2, in Bydgoszcz. This study was designed as a questionnaire survey and included the Skindex-29 instrument for the assessment of quality of life in patients with dermatological conditions. Results : Overall, the global Skinndex-29 scores of all studied participants ranged between 37 and 136 points, 23.93 points on average. The analyzed groups of patients differed significantly with respect to the average level of the global quality of life determined using the Skindex-29 questionnaire. Conclusions : Significant differences were observed in the global quality of life of patients who suffered from venous or arterial leg ulcers or skin lesions resulting from chronic venous insufficiency.